Research on Optimization Design of Front and Side Structures under the 24th Edition of C-NACP Automotive Collision Standard - Cao, Huan (International Journal of Mechanical and Electrical Engineering, 2024)
Structural crashworthiness plays a core role in vehicle safety design, mainly focusing on the maximum impact force that the body structure can withstand in collision accidents, and striving to maximize collision energy absorption to ensure that passengers have sufficient living space. The design of structural crashworthiness needs to consider the deformation mechanism and energy absorption characteristics of vehicles under different collision modes, and improve crashworthiness through material selection, structural optimization, and other means. In addition, the structural crashworthiness is closely connected to the passenger restraint system, which together constitute the key to the passive safety performance of the vehicle. In vehicle safety design, the improvement of structural crashworthiness can significantly enhance the vehicle’s ability to protect passengers in collision accidents and reduce the risk of injury. Therefore, in-depth research on structural crashworthiness and the development of efficient crashworthiness structures are important directions for improving vehicle safety performance.